2009
DOI: 10.2337/db08-1299
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Induced During Adipogenesis that Accelerate Fat Cell Development Are Downregulated in Obesity

Abstract: OBJECTIVE-We investigated the regulation and involvement of microRNAs (miRNAs) in fat cell development and obesity.RESEARCH DESIGN AND METHODS-Using miRNA microarrays, we profiled the expression of Ͼ370 miRNAs during adipogenesis of preadipocyte 3T3-L1 cells and adipocytes from leptin deficient ob/ob and diet-induced obese mice. Changes in key miRNAs were validated by RT-PCR. We further assessed the contribution of the chronic inflammatory environment in obese adipose tissue to the dysregulated miRNA expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
539
2
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 536 publications
(593 citation statements)
references
References 49 publications
45
539
2
7
Order By: Relevance
“…A wide number of miRNAs, such as miR-103 and miR-143 increase during in vivo and in vitro adipocyte differentiation and their ectopic expression increases adipogenesis. 109 Interestingly, these miRNAs were found to be downregulated in mouse models of obesity, thus suggesting that they play a role in phenotypic maintenance and function of mature adipose cells. Another report showed downregulation of miR-31, miR-125b-5p and miR-326 during adipocyte differentiation from adipose-derived stem cells, suggesting a role for these miRNAs in this process.…”
Section: Differentiation Of Preadipocytesmentioning
confidence: 99%
“…A wide number of miRNAs, such as miR-103 and miR-143 increase during in vivo and in vitro adipocyte differentiation and their ectopic expression increases adipogenesis. 109 Interestingly, these miRNAs were found to be downregulated in mouse models of obesity, thus suggesting that they play a role in phenotypic maintenance and function of mature adipose cells. Another report showed downregulation of miR-31, miR-125b-5p and miR-326 during adipocyte differentiation from adipose-derived stem cells, suggesting a role for these miRNAs in this process.…”
Section: Differentiation Of Preadipocytesmentioning
confidence: 99%
“…Because microRNAs (miRNAs) have been shown to be important in gene regulation, it is not surprising that they have been implicated in the development of obesity (Williams and Mitchell 2012). Therefore, the understanding of the regulatory Several miRNAs expression patterns have been profiled during adipocyte differentiation (Kajimoto et al 2006;Xie et al 2009;Ortega et al 2010), others have been linked to adipocyte phenotype, and other obesity parameters (Kajimoto et al 2006;Takanabe et al 2008;Klöting et al 2009;Xie et al 2009;Ortega et al 2010;Heneghan et al 2011;Keller et al 2011;Ortega et al 2013) (Figure 2). For example, miR-21 was strongly expressed in human adipose tissue and positively correlated with BMI (Keller et al 2011).…”
Section: Micrornasmentioning
confidence: 99%
“…Although basic studies have highlighted the significance of miRNAs in the regulation of obesity and insulin resistance (13,14,15,16), few studies have investigated circulating miRNAs levels as potential biomarkers for obesity in humans. Recently, Ortega et al (17) have revealed that plasma miR-142-3p, miR-140-5p, miR-15a, miR-520c-3p, and miR-423-5p may constitute novel biomarkers for risk estimation and classification of morbidly obese patients.…”
Section: Introductionmentioning
confidence: 99%